Evolution and Impact of Forensic DNA Typing in Modern Investigation - Umer Ali; Nabila Iqbal; Hafiza Rabia Shafiq; Husnain Ahmad; Arooj Asalm; Asad Abbas; Kashif Nawaz; Sarmad Yousaf; Muhammad Kaleem Ullah (International Journal of Molecular Biotechnological Research, 2024)
Forensic DNA typing is sometimes called DNA fingerprinting. Immigration, paternity, and criminal investigations use forensic DNA typing. Forensic genetics today includes bodily fluid identification, fast DNA analysis, forensic microbiology, and phenotypic profiling. Human cells contain DNA, a molecular code. Human DNA sequences are 99.9% the same in everyone. Every person has almost 0.1% unique DNA. Forensic experts also worry about this 0.1 percent of DNA that is unique. There are several steps undertaken during the analysis of forensic DNA. These steps are sample preparation, DNA extraction, amplification, quantification, and DNA profile matching. Parentage testing, mass tragedies, and crime scene investigations have relied on forensic DNA techniques. An individual's genetic makeup is built on DNA. DNA can be isolated from living and dead people due to its stability. Using DNA from crime scene samples, forensic DNA phenotyping shows a person's biogeography, ancestry, appearance, and age. It is experienced in criminal situations where forensic STR (Short Tandem Repeat) profiling has no match since the donor sample is unknown to the investigators. In his leukocyte cellular function research, Friedrich Miescher extracted DNA from cellular components and proteins. The precipitate Friedrich found was completely different from the protein. He extracted protein using basic composition analysis. Washing the leukocyte with HCl for weeks isolates the nuclei in water/ether. In this research, we try to discuss DNA damage and repair recycling. Forensic DNA typing has transformed criminal investigations and resolutions. This technique has exonerated the wrongfully condemned, provided strong evidence of guilt for suspects, and identified prospective culprits using DNA databases in unresolved instances. However, alongside these advancements come challenges that must be addressed to fully realize the potential of forensic DNA analysis. One such challenge is the need for education and training to improve the interpretation of complex DNA profiles generated by next-generation sequencing (NGS) technologies. As these technologies become more widespread, forensic analysts must be equipped with the knowledge and skills to accurately interpret the wealth of data produced. However, alongside these advancements come challenges that must be addressed to fully realize the potential of forensic DNA analysis. One such challenge is the need for education and training to improve the interpretation of complex DNA profiles generated by NGS technologies.
Keywords: Forensic; emergence; extracted; investigation; profiling; statistical